2023
DOI: 10.1007/s40121-023-00823-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of 8-Week Glecaprevir/Pibrentasvir in Treatment-Naïve, Compensated Cirrhotic HCV Patients

Abstract: Introduction The EXPEDITION-8 clinical trial has demonstrated that treatment-naïve patients with compensated cirrhosis (TN/CC) of HCV genotypes 1–6 can achieve a 98% intent-to-treat sustained virologic response rate 12 weeks post-treatment with an 8-week glecaprevir/pibrentasvir (G/P) regimen. Further real-world evidence is needed to support the effectiveness of 8-week G/P in a clinical practice setting and to consolidate these treatment recommendations. The aim of this study is to contribute real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…These results are consistent with those of the EXPEDITION-8 clinical trial of an 8-week GLE/PIB regimen in treatment-naïve patients without cirrhosis (99.7% in the per-protocol sample and 97.7% in the ITT sample) [ 4 ]. They are likewise consistent with a number of “real-world” studies of patients in Taiwan [ 6 ] and the US Veterans’ Administration [ 7 , 9 ], as well as a recent study drawn from a large US administrative database [ 8 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are consistent with those of the EXPEDITION-8 clinical trial of an 8-week GLE/PIB regimen in treatment-naïve patients without cirrhosis (99.7% in the per-protocol sample and 97.7% in the ITT sample) [ 4 ]. They are likewise consistent with a number of “real-world” studies of patients in Taiwan [ 6 ] and the US Veterans’ Administration [ 7 , 9 ], as well as a recent study drawn from a large US administrative database [ 8 ].…”
Section: Discussionsupporting
confidence: 87%
“…One USA-based study of an 8-week regimen in treatment-naïve patients with cirrhosis demonstrated a 96% SVR rate [ 7 ], but no safety data were collected and there was no comparison group. Likewise, a recent study using a large administrative database found that an 8-week regimen was effective in treatment-naïve patients with cirrhosis but did not include data regarding adverse events [ 8 ]. Another study in a Veterans Administration population [ 9 ] was overwhelmingly (97%) male and included a large proportion of patients without cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of glecaprevir/pibrentasvir has been highly effective in drug users, with an SVR of 93%. In other patients, the SVR was around 95% [110].…”
Section: Velpatasvir and Pibrentasvirmentioning
confidence: 91%
“…The introduction of DAAs marked a revolutionary step in HCV management, with cure rates above 95% and defining SVR, specifically undetectable HCV RNA 12 weeks post-treatment (SVR12), as a new clinical benchmark instead of 24 weeks [ 306 , 307 ]. Additionally, 8-week regimens have shown effectiveness in real-world studies, with a positive impact on treatment adherence and reduction in costs [ 308 , 309 , 310 ]. DAAs offer the enhancement of patient tolerability to treatment and allow for the customization of treatment regimens based on individual patient factors such as HCV genotype, stage of liver fibrosis, co-existing medical conditions, prior treatment history, and potential RASs [ 311 , 312 ].…”
Section: Treatment Of Hcvmentioning
confidence: 99%